Answer:
Step-by-step explanation:
We know:
[tex]f\bigg(f^{-1}(x)\bigg)=x[/tex]
Therefore
[tex]f\bigg(f^{-1}(3)\bigg)=3[/tex]
Other method.
Find [tex]f^{-1}(x)[/tex]
[tex]f(x)=3x+12\to y=3x+12[/tex]
exchange x to y and vice versa:
[tex]x=3y+12[/tex]
solve for y:
[tex]3y+12=x[/tex] subtract 12 from both sides
[tex]3y=x-12[/tex] divide both sides by 3
[tex]y=\dfrac{x-12}{3}\to f^{-1}(x)=\dfrac{x-12}{3}[/tex]
[tex]f\bigg(f^{-1}(x)\bigg)[/tex] replace x in f(x) with the expression [tex]\dfrac{x-12}{3}[/tex]
[tex]f\bigg(f^{-1}(x)\bigg)=3\cdot\dfrac{x-12}{3}+12=x-12+12=x[/tex]
[tex]f\bigg(f^{-1}(3)\bigg)[/tex] - put x = 3 to [tex]f\bigg(f^{-1}(x)\bigg)[/tex]
[tex]f\bigg(f^{-1}(3)\bigg)=3[/tex]